Neuroprotective Strategies in Glaucoma - A. Gossman, Cynthia; Christie, John; K. Webster, Mark; M. Linn, David; L. Linn, Cindy (Current Pharmaceutical Design, 2016)
Background: Glaucoma is characterized as a neuropathic disease that causes progressive degeneration of retinal ganglion cells (RGCs) in the retina, resulting in irreversible loss of vision. All conventional treatments for glaucoma are focused on reducing intraocular pressure (IOP) in the anterior chamber of the eye. However, these treatments alone are insufficient to halt the progression of the disease. As a result, neuroprotective strategies have been developed that prevent retinal neuron loss and disease progression. Methods: The goal of this review is to summarize and discuss neuroprotective strategies in glaucoma at the level of the retina and the ganglion cell layer instead of treatments targeting IOP. Recent and past neuroprotective therapies used to prevent the loss of retinal ganglion cells, the loss of axons in the optic nerve and the loss of vision and function associated with glaucoma are presented. Results: Pharmacological approaches have targeted specific receptors, signaling cascades and neurotrophic factors to induce neuroprotection in the retina, while others have focused on the mechanism of cellular loss associated with glaucoma, including excitotoxicity, oxidative stress and apoptotic processes. In addition to neuroprotective pharmacological treatments, stem cell, gene therapy and viral research have demonstrated neuroprotection against the loss of RGCs in glaucomatous conditions. Conclusion: It is likely that future development for glaucoma treatment will include a combination of these treatments to prevent the pathophysiology of glaucoma.
Keywords: gene therapy